2018
DOI: 10.1186/s12889-018-5285-0
|View full text |Cite
|
Sign up to set email alerts
|

Antenatal care satisfaction in a developing country: a cross-sectional study from Nigeria

Abstract: BackgroundUtilization of Antenatal Care (ANC) is very low in Nigeria. Self-reported patient satisfaction may be useful to identify provider- and facility-specific factors that can be improved to increase ANC satisfaction and utilization.MethodsExit interview data collected from ANC users and facility assessment survey data from 534 systematically selected facilities in four northern Nigerian states were used. Associations between patient satisfaction (satisfied, not-satisfied) and patient ratings of the provid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
40
5
5

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(58 citation statements)
references
References 24 publications
8
40
5
5
Order By: Relevance
“…terhadap kualitas pelayanan asuhan kehamilan di fasilitas kesehatan yaitu layanan klinik, aksesibilitas klinik dan interaksi dokter yang merupakan kontributor penting untuk kepuasan perawatan prenatal. (Adeyinka et al, 2017;Chemir et al, 2014;Ejigu et al, 2013;Nwaeze et al, 2013;Onyeajam et al, 2018).…”
Section: Pembahasanunclassified
“…terhadap kualitas pelayanan asuhan kehamilan di fasilitas kesehatan yaitu layanan klinik, aksesibilitas klinik dan interaksi dokter yang merupakan kontributor penting untuk kepuasan perawatan prenatal. (Adeyinka et al, 2017;Chemir et al, 2014;Ejigu et al, 2013;Nwaeze et al, 2013;Onyeajam et al, 2018).…”
Section: Pembahasanunclassified
“…Pelaksanaan Antenatal Care di beberapa Negara dilaporkan masih rendah seperti di beberapa Negara bagian di Nigeria seperti dilaporkan dalam jurnal oleh (Onyeajam, Xirasagar, Khan, Hardin, & Odutolu, 2018). Hal ini ditunjukkan dari kepuasan pasien yang sangat dipengaruhi oleh beberapa faktor yaitu dalam pelayanan seperti jam buka, ruang yang nyaman, pelayanan yang terburu buru dan respon layanan yang cepat, ketersediaan alat, sikap empati, non diskriminatif serta komunikasi pemberi layanan.…”
Section: Latar Belakangunclassified
“…Studies have suggested that low rate of ANC attendance and institutional delivery in most developing countries are borne by the dissatisfaction pregnant women experience from caregivers [8]. Thus, the quality of ANC services sustainably provided to pregnant women is vital [9].…”
Section: Introductionmentioning
confidence: 99%
“…Some studies including [9,[14][15][16][17][18][19][20][21][22][23] have reported on direct correlation between antenatal care visits and clients' satisfaction. As reported by [24] in Ghana, the free maternal healthcare policy was irst introduced in September 2003 as a pilot project in the central, upper east, upper west, and the northern regions.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation